Examining Dietetic Students' Feedback on Integrated Simulation-Based Education and Objective Structured Clinical Examination: A Mixed-Methods Approach: A Mixed-Methods Analysis of Dietetic Students' Perspectives on Integrated Simulation-Based Education and Objective Structured Clinical Examination - Khalifa, Nahla; Aljaaly, Elham (Journal of King Abdulaziz University: Medical Sciences, 2023)
Background: Objective Structured Clinical Examination (OSCE) and simulated-based learning (SBL) are feasible models to assess and improve students’ clinical skills. Objectives: To evaluate the Saudi dietetic students' perceptions of the implemented structured clinical education approaches (OSCE) and (SBL) effectiveness. The primary focus is evaluating gained competencies and readiness for future clinical placements. Methods: The study implemented a developed and validated electronic survey to evaluate the executed OSCE and SBL approaches in King Abdulaziz University's dietetic program in Jeddah, Saudi Arabia. Dietetic seniors (n=37) completed an online survey with open and closed-ended questions after completing the 2018-2019 academic year clinical education course. Statistical analysis included descriptive data that are summarized using frequencies and percentages. Content Analysis was utilized for the students' reflections and feedback. Results: 182% response rate, 37 students recruited, and 45 responses received (some did double survey). Results (95.6%, n=43) indicate that the implemented approaches effectively prepared students for the practical application of learned theories and concepts in managing inpatient cases. Students combined and contrasted information from different resources with confidence (86.5%, n=32) and made evidence-based decisions in patient nutrition management. Eighty-nine percent of students were familiar with the abbreviation OSCE, with 88.9% (n=40) stating that they found the OSCE stressful and 91% felt well-prepared for future clinical placement and supported continuing the approach in the next academic year. Conclusion: Dietetic seniors' positive feedback highlights the significance of incorporating well-structured SBL sessions and OSCE exams in dietetic education in the academic year 2018-2019. Keywords: Competencies, Dietetics, OSCE, Simulated-based. King Abdulaziz University.